2020
DOI: 10.1364/prj.399926
|View full text |Cite
|
Sign up to set email alerts
|

All-metallic metasurfaces towards high-performance magneto-plasmonic sensing devices

Abstract: Magneto-plasmonic sensors based on surface plasmon resonance have been studied considerably in recent years, as they feature high sensitivity and ultrahigh resolution. However, the majority of such investigations focus on prism-based sandwich architectures that not only impede the miniaturization of devices but also have a weak transverse magneto-optical Kerr effect (TMOKE) in magnitude. Herein, we theoretically demonstrate a magneto-plasmonic sensor composed of Au/Co bilayer nanodisk arrays on top of opticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…The fabrication of a periodic square array of Au/Co bilayer nano-disks on an optically thick metallic substrate results in the demonstration of a high-performance magnetoplasmonic sensor [ 82 ]. This results in the formation of an ultranarrow SPR mode with a full width at half maximum of 7 nm and RI sensitivity as high as 717 nm/R.I.U, whose high-quality resonance characteristic is like the surface lattice resonance linked to the far-field coupling between nano-objects.…”
Section: Types Of Ms-based Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fabrication of a periodic square array of Au/Co bilayer nano-disks on an optically thick metallic substrate results in the demonstration of a high-performance magnetoplasmonic sensor [ 82 ]. This results in the formation of an ultranarrow SPR mode with a full width at half maximum of 7 nm and RI sensitivity as high as 717 nm/R.I.U, whose high-quality resonance characteristic is like the surface lattice resonance linked to the far-field coupling between nano-objects.…”
Section: Types Of Ms-based Sensorsmentioning
confidence: 99%
“…Nevertheless, the few linked earlier investigations have shown that hafnium nitride has better plasmonic efficiency for photothermal applications relative to gold and even titanium nitride [ 80 ].
Figure 2 Types of MS such as ( a ) All-dielectric MS [ 81 ], ( b ) All-metallic MS [ 82 ], and ( c ) Hybrid MS [ 83 ], for biosensing [ 84 ], gas sensing [ 85 ], and temperature sensing applications [ 86 ].
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the influence of the Fano transmission spectrum on the RI was further studied, which provides the possibility for the study on optical sensors [37,38]. Figure 3A shows the Fano transmission lines of the waveguide with different RI (n = 1-1.08).…”
Section: Sensing Performance Analysismentioning
confidence: 99%
“…Metamaterial absorbers (MAs) typically consist of three layers in a metal-dielectric-metal (MDM) structure, i.e., the patterned metal antenna and the thick metal mirror layers are separated by a thin dielectric spacer. [9][10][11][12][13][14][15] The MDM structure is ideal for designing an MPA, for this kind of structure of MPA can store the internal electromagnetic energy and then dissipate it gradually. The unitary structure of the MDM absorber, also known as a meta-atom, primarily has a regular and simple geometry, including squares, 16 rectangles, 17 crosses 18 and circles.…”
Section: Introductionmentioning
confidence: 99%